2011
DOI: 10.1002/cncr.26498
|View full text |Cite
|
Sign up to set email alerts
|

Interval to biochemical failure as a biomarker for cause‐specific and overall survival after dose‐escalated external beam radiation therapy for prostate cancer

Abstract: BACKGROUND:After external beam radiation therapy (EBRT) for prostate cancer, a short interval to biochemical failure of <18 months has been proposed as a surrogate for cause‐specific survival. Because EBRT dose influences biochemical failure, the authors investigated the interval to biochemical failure in a cohort of patients treated with dose‐escalated EBRT.METHODS:From 1998 to 2008, 710 patients were treated with EBRT (≥75 grays) ± androgen deprivation therapy (ADT) at the University of Michigan. Biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Nevertheless, the role of treatment effect in our study can be extrapolated from previous findings after EBRT with or without hormone use (6,12,13,17,18). Most recently, Kapadia et al (21) and Ray et al (12) demonstrated a short interval to biochemical failure after completing EBRT that correlated with a significantly increased rate of biochemical failure and DM as compared with a longer interval to biochemical failure or lack of biochemical failure. Ray et al (12) also noted that dose higher than 70 Gy was associated with not only a lower nPSA level but also a longer TnPSA, and that greater dose was significantly associated with greater PSA-DFS and distant metastasis-free survival (12).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the role of treatment effect in our study can be extrapolated from previous findings after EBRT with or without hormone use (6,12,13,17,18). Most recently, Kapadia et al (21) and Ray et al (12) demonstrated a short interval to biochemical failure after completing EBRT that correlated with a significantly increased rate of biochemical failure and DM as compared with a longer interval to biochemical failure or lack of biochemical failure. Ray et al (12) also noted that dose higher than 70 Gy was associated with not only a lower nPSA level but also a longer TnPSA, and that greater dose was significantly associated with greater PSA-DFS and distant metastasis-free survival (12).…”
Section: Discussionmentioning
confidence: 61%
“…The use of HDR brachytherapy is now widely used and accepted in the United States and worldwide (22). The PDR brachytherapy combined with EBRT is emerging as a potentially advantageous modality as it has a lesser source strength and hence lower requirements for surrounding shielding, yet potentially provides equivalent cancericidal effects and normal tissue sparing to other brachytherapy modalities (20,21). In our study, PDR brachytherapy equipment was used in an HDR technique, in which a 1 Ci 192 Ir source delivered dose in three large fractions rather than multiple small fractions, the rationale of which is outlined in our previous reports (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For cancer-related outcomes, all four studies investigating DM or PCSM as outcome showed a significant negative impact of BCR with varying impact. In contrast, the impact of BCR on OM is less clear, but still five out of eight studies report an impact of BCR on OM rates [16,17,79,87,88] while the other three studies do not show this effect [15,18,19].…”
Section: Impact Of Bcr On Oncological Outcomes (Objective 1)mentioning
confidence: 94%
“…In addition to metastasis, which could have influenced A2 failures and led to worse clinical outcomes, early BF (with a short interval to BF) has also been identified as carrying a significantly increased risk of death from prostate cancer 24,25 or death overall. 26 and it may have been captured in the A2 definition, particularly for those men who had continually rising PSA after RT or recurrence even during ADT.…”
Section: Discussionmentioning
confidence: 99%